Long-term remissions of young patients with high-risk follicular lymphoma after first-line autologous stem cell transplantation: Three case reports. Issue 22 (29th May 2020) - Lyu, Rui; Wang, Tingyu; Zou, Dehui; Liu, Wei; Yi, Shuhua; Huang, Wenyang; An, Gang; Xu, Yan; Li, Zengjun; Qiu, Lugui
Abstract: Rationale: Autologous stem cell transplantation (ASCT) is not routinely recommended as first-line choice for follicular lymphoma (FL). However, we actually have observed that young patients with extremely high-risk factors benefit from ASCT. This study aims to speculate the rationality of ASCT as first-line treatment, through 3 cases and review of the literature. Patient concerns: 3 young-adult patients with FL received ASCT as first-line treatment. Diagnosis: All the 3 patients were no more than 30 years old and the diagnosis of FL was confirmed by histopathological and immunohistochemical evaluations. They all had multi-organ involvements, and two of them presented with a "leukemic-like" manifestation. Compared with those in the previous literatures, the 3 patients were relatively younger and had more invasive clinical features. Interventions: The 3 patients received combined chemotherapy plus rituximab, followed by first-line ASCT. Outcomes: All the 3 patients got complete remission and minimal residual disease negativity after ASCT, The median follow-up time was 109 (97–117) months, and all of them were in remission more than 8 years after transplant. Lessons: Guidelines for FL are mainly based on elderly patients, but are not suitable enough for all, especially for the young FL patients. For young patients with certain high-risk FL, first-line ASCT does not go against the guidelines, and should be recommended individually.